Morfogênese in vitro e triagem fitoquímica de Myracrodruon urundeuva Fr. All. - Silva, Tecla dos Santos (2017)
Myracrodruon urundeuva Fr. All. (Anacardiaceae) is an endangered tree that has wood and medicinal potential. This work aimed to study the induction of in vitro buds of M. urundeuva and to analyze the calogenesis process, as well as qualitatively evaluate the chemical composition of different organs of the species submitted to different culture conditions. In the induction of shoots, silver nitrate (AgNO3) and plant regulators 6-benzylaminopurine (BAP), kinetin (KIN), meta-topoline (mT) and naphthaleneacetic acid (NAA) were evaluated using different explants (cotyledons, petiole, nodal, cotyledonary and apical segments). For calogenesis, combinations of 2,4-D, KIN and glutamine in leaf explants were tested. The callus growth curve was performed for 56 days (7 day intervals) and the reducing sugars (RS), sucrose and total soluble sugars (TSS) were quantified. For the phytochemical study, we used methanolic extracts from material grown in vitro, in a greenhouse and in a natural environment. It is possible the induction of buds in M. urundeuva from the explant cotyledon node with the use of BAP combined with NAA. Calogenesis is potentiated with the combination of 2,4-D, KIN and glutamine in the nutrient medium. The growth curve of the callus is sigmoidal. The carbohydrate content, except for RA, presents a distinct behavior, varying according to the growth curve phases of the callus. The type of cultivation influences the yield of extracts of M. urundeuva and there are differences in the production of secondary metabolites between the different organs of the species.